NEW TECHNOLOGIES AND THE DISCOURSES OF HUMAN RIGHTS, POLITICS, AND SOCIETY - Goran Ilik (Institute for Research and European Studies, 2021)
Modern societies are associated with the constant flow and acceptance of information and communication technologies at home, in the workplace, in the process of education, even in recreational activities. The development of new technologies has not only challenged human rights, but also politics and society in general. Even more importantly, this new technological level has also empowered transnational corporations operating in the digital environment as hosting providers to perform quasi-public functions in the transnational context. New technologies have the potential to make significant positive contributions to the prevention, promotion, and protection of human rights and democratization, decentralization, and digitalization of politics and the advancement of society as a whole.